2003
DOI: 10.1093/jurban/jtg053
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Study to Enhance HIV Care Using Needle Exchange-Based Health Services for Out-of-Treatment Injecting Drug Users

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(62 citation statements)
references
References 51 publications
0
62
0
Order By: Relevance
“…Moreover, syringe-exchange programs have the opportunity to engage active drug users in other positive health behaviors, such as entry into drug treatment [23,24], provision of methadone maintenance therapy [25,26], direct delivery of health care services [24,[27][28][29], and provision of antiretroviral therapy [30]. Through its continuous contact with and nonjudgmental approach to drug users, health services located at sites of syringe exchange could incorporate treatment for HIV infection, particularly directly administered antiretroviral therapy (DAART).…”
mentioning
confidence: 99%
“…Moreover, syringe-exchange programs have the opportunity to engage active drug users in other positive health behaviors, such as entry into drug treatment [23,24], provision of methadone maintenance therapy [25,26], direct delivery of health care services [24,[27][28][29], and provision of antiretroviral therapy [30]. Through its continuous contact with and nonjudgmental approach to drug users, health services located at sites of syringe exchange could incorporate treatment for HIV infection, particularly directly administered antiretroviral therapy (DAART).…”
mentioning
confidence: 99%
“…Strategies to increase access to and utilization of HAART have included entry into drug treatment, abstinence, community outreach and referral, and provision of medical care at nontraditional sites such as syringe exchange (Molitor et al, 2005). For example, Altice, Springer, Buitrago, Hunt, and Friedland (2003) provided HAART to out-of-treatment IDUs using a mobile van at SEP sites and found that by 6 months the proportion whose HIV-1 RNA was below the limits of detection was 85%; 77% had no detectable levels by 9 months.…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacologic (eg, methadone program, buprenorphine treatment program) [42] and/ or nonpharmacologic treatment (eg, Twelve Steps programs) for substance use [43] 2. Flexible outpatient and community care settings (eg, walk-in clinics, mobile health care programs) [44] 3. Low-threshold sites to engage active users (eg, syringe-exchange sites) [45] 4.…”
Section: Treatment Of Hiv Infection In Drug Usersmentioning
confidence: 99%